Effect of value addition to rice straw on the nutritional improvement and milk productivity of dairy cattle (Bangladesh Journal of Animal Science, 2020)
The objective of this study was to evaluate the physical and chemical value addition to rice straw on nutritional quality improvement of rice straw and its effect on milk productivity and composition. Twelve crossbred milking cows (Frisian Cross) of mid-lactation stage and second parity, having average initial body weight of 398.72 ± 42.22 kg and milk yield of 6.42± 0.78 kg were assigned to three treatment group (each group has 4 animals) and one control group. Four treatments were considered: T0 (control): loose rice straw + green grass + concentrate; T1: value addition to rice straw through chopping (physical) + green grass + concentrate; T2: value addition to rice straw through urea and molasses without chopped (Chemical) + green grass + concentrate; and T3: value addition to rice straw through urea molasses with chopping (Physical and chemical) + green grass + concentrate. The results revealed that T2 was significantly (p